2020
DOI: 10.3390/cells9040999
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Mislocalization of Nuclear Membrane-Associated Proteins in γ-Irradiation-Induced Senescent Cells

Abstract: Cellular senescence, induced by genotoxic or replication stress, is accompanied by defects in nuclear morphology and nuclear membrane-heterochromatin disruption. In this work, we analyzed cytological and molecular changes in the linker of nucleoskeleton and cytoskeleton (LINC) complex proteins in senescence triggered by γ-irradiation. We used human mammary carcinoma and osteosarcoma cell lines, both original and shRNA knockdown clones targeting lamin B receptor (LBR) and leading to LBR and lamin B (LB1) reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…As cell cycle checkpoint pathways, the maintenance of the homeostasis between the nuclear envelope and telomeres may be tightly regulated and important for cell cycle progression. Interestingly, a recent study showed that the mislocalization of LINC complex proteins is a significant characteristic of cellular senescence [ 84 ]. Notably, RAP1 S205 phosphorylation, which is activated by p90RS activation, induces the nuclear export of the RAP1-TRF2 complex and further contributes to senescence and telomere dysfunction in epithelial cells [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…As cell cycle checkpoint pathways, the maintenance of the homeostasis between the nuclear envelope and telomeres may be tightly regulated and important for cell cycle progression. Interestingly, a recent study showed that the mislocalization of LINC complex proteins is a significant characteristic of cellular senescence [ 84 ]. Notably, RAP1 S205 phosphorylation, which is activated by p90RS activation, induces the nuclear export of the RAP1-TRF2 complex and further contributes to senescence and telomere dysfunction in epithelial cells [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distribution pattern of nuclear envelope (NE) protein is an important prerequisite for its biological functions [30][31][32] . To this end, we first investigated how actomyosin contractility affects the distribution of SUN2 on the nuclear membrane.…”
Section: Actomyosin Contractility Level Regulates the Ratio Of Sun2 D...mentioning
confidence: 99%